The genome sequence of the White-barred Gold, Micropterix aruncella (Scopoli, 1763) - Holland, PWH; Hammond, J; Holland, AS (F1000 Research Ltd, 2023)
We present a genome assembly from an individual female Micropterix aruncella (the White-barred Gold; Arthropoda, Insecta, Lepidoptera; Micropterigidae). The genome sequence is 1,079 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the assembled Z sex chromosome. The mitochondrial genome has also been assembled and is 15.0 kilobases in length.